Four decades of transmission of a multidrug-resistant Mycobacterium tuberculosis outbreak strain - Eldholm, Vegard (2015)
Fil: Eldholm, Vegard. Norwegian Institute of Public Health. Division of Infectious Disease Control; Noruega.